The impact of thermal ink jet printing within one selected fast moving consumer goods organisation in SA: a feasibility study - Germanus, Wayne Luke (My University, 2020)
The primary objective of this research was to investigate the impact of thermal inkjet (TIJ) printing technology within a fast moving consumer goods organisation in SA, using Company 1 which consisted of 5 separate factories, as the selected organisation for the study. This was achieved by using the reliability, availability, maintainability and safety (RAMS) methodology as a basis in determining the current and future key performance indicators (KPIs) that were critical to the success of the organisation. Qualitative and quantitative research methods were used by allowing 15 employees at Company 1 to participate in an online survey, while a separate face-to-face interview was also conducted with a coding and marking supplier, known as Supplier 1. Based on the feedback received, it was discovered that the current printing technologies in use at Company 1–which consisted of print-and apply, thermal transfer overprinting (TTO) and continuous inkjet (CIJ) technology–should include KPIs that measure label consumption, ribbon reel consumption ,ink and solvent costs, line downtime, repairs and support costs, maintenance costs and working capital respectively. Furthermore, the KPIs that were most critical to measuring the success of future printing technologies, under the assumption that Company 1 invested entirely in TIJ technology, included ink cartridge costs, line downtime and operational efficiency. The second objective involved calculating the total cost of ownership (TCO) assuming Company 1 were to utilise TIJ technology at each of its5 factories. The TCO results indicated that TIJ technology would prove to be a more cost effective printing technology in the long term on the corrugate, carton and horizontal-form-fill-and-seal flexible packaging format at every factory, due to the significantly reduced maintenance costs involved. The only exception was Factory 5’s flexible packaging format, which predominantly utilised a vertical-form-fill-and-seal arrangement, which proved to be better suited to TTO technology
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science in Engineering, 2020